2018
DOI: 10.1186/s12882-018-1153-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glomerular filtration rate, high grade albuminuria and associated factors among adult patients admitted to tertiary Hospital in Ethiopia

Abstract: BackgroundChronic Kidney Disease (CKD), the worldwide Public Health problem, is also one of the rising non-communicable diseases in low and middle-income countries. Its early detection and treatment using readily available, inexpensive therapies can slow or prevent progression to end-stage renal disease. Hence, this study was aimed at assessing impaired estimated glomerular filtration rate (eGFR), high grade albuminuria, and associated factors among adult patients admitted to Jimma University Medical Center in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
3
7
1
Order By: Relevance
“…34,35 In our study, the risk of having CKD was higher among those with a history of hypertension than those who do not have. This finding is consistent with several related studies, 23,[36][37][38] which reported hypertension as the main risk factor of CKD. This could be due to the kidney being unable to function properly unless adequately perfused with intact blood stream.…”
Section: Discussionsupporting
confidence: 94%
“…34,35 In our study, the risk of having CKD was higher among those with a history of hypertension than those who do not have. This finding is consistent with several related studies, 23,[36][37][38] which reported hypertension as the main risk factor of CKD. This could be due to the kidney being unable to function properly unless adequately perfused with intact blood stream.…”
Section: Discussionsupporting
confidence: 94%
“…Although there is still uncertainty about the root cause of CKD, studies suggest that numerous risk factors are responsible for CKD, such as obesity [ 6 11 ], old age [ 7 9 , 11 14 ], hypertension [ 3 , 7 , 9 13 , 15 17 ], diabetes mellitus [ 3 , 7 , 8 , 10 12 , 16 , 18 ], male gender [ 12 , 17 ], hyperlipidemia [ 7 ], use of nephrotoxic medications [ 7 ], family history of kidney disease [ 9 , 11 , 13 ], smoking [ 19 ], heavy drinking [ 19 ], HIV infection [ 13 ], electrolyte and acid-base disturbances [ 13 ], low-income occupation, use of traditional medication, and low hemoglobin [ 11 ]. Early detection and treatment of possible risk factors are readily available and often inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…The highest magnitude of CKD is reported from Jimma University medical center (38.9%) 29 while the least is from Zewditu memorial hospital (12.2%). 30 The studies were conducted in five different regions of the country; 4 from Addis Ababa, 19 , 26 , 30 , 31 4 from Amhara, 20 , 21 , 27 , 28 2 from Oromia, 22 , 29 and 1 from SNNPR. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Some of them are cholesterol level, 18 body mass index (BMI), 18 , 19 uncontrolled blood pressure age > 60, duration of noncommunicable diseases, 20 , 21 and residence. 22 …”
Section: Introductionmentioning
confidence: 99%